Effect of visually cued spatial and temporal attention on audiovisual stimuli processing: an event-related potentials study - Yang Feng; Kai Liu; Rui Zhang; Huiyuan Wang; Yulin Gao; Zhihan Xu; Jingjing Yang (Frontiers in Psychology)
IntroductionPrevious studies have investigated the effect of spatial and temporal attention on visual or auditory stimulus processing. The visual and auditory information received simultaneously from different modalities must be integrated by several systems to produce coherent cognition in the brain. However, how spatial and temporal attention modulates audiovisual (AV) stimuli processing is still unclear.MethodsThe aim of this study was to compare the modulatory effects of spatial attention versus temporal attention on audiovisual stimuli processing using event-related potentials (ERPs) with high temporal resolution. Spatial attention was triggered by a visual spatial cue (usually an arrow), and temporal attention was triggered by a visual temporal cue (two concentric circles).ResultsBehavioral responses to audiovisual stimuli in the spatial attention condition were faster than those in the temporal attention condition, and the false alarm rate in the spatial attention condition was lower than that in the temporal attention condition. The ERP results show that the amplitude of N2 elicited by AV stimuli in the right temporal and right occipital areas in the spatial attention condition was greater than that in the temporal attention condition.DiscussionThese results indicate that spatial and temporal attention have a differential effect on AV stimuli processing in the right occipitotemporal area.